Peningkatan Kapasitas Kader PKK Dalam Implementasi Program IDEAL Untuk Penanggulangan Obesitas Di Desa Kesiman Kertalangu Denpasar. - Wiardani, Ni Komang; Kusumajaya, Anak Agung Ngurah; Ari Widarti, I Gusti Ayu (Poltekkes Kemenkes Denpasar, 2024)
Backround : Obesity is a problem experienced by people in the city of Denpasar due to unhealthy lifestyles. Obesity can increase non-communicable diseases such as heart disease, DM, and stroke. The Integration of Diet, Nutrition Education, Physical Activity and Training (IDEAL) program as a follow-up to research can be implemented by empowering PKK cadres as program implementers. Community service activities aim to improve the skills of PKK cadres in implementing the IDEAL program to prevent obesity in the community. The target of the activity was 40 PKK cadres in Kesiman Kertalangu Village. Activities are carried out through educational programs, group exercises, and improving skills in preparing a balanced nutritional diet. Activities will be carried out for 3 months (June – September 2022). with education, group exercise every month, and the practice of preparing a balanced menu. A pretest and posttest were conducted on nutritional status, knowledge, and skills in preparing a balanced menu. Results: in PKM activities the results obtained were that the average age of PKK cadres was 45.4 years, BMI 24.9 kg/m2, waist circumference 82.6 cm. The results of the pre-test on target knowledge were with a score of 73.6 (fairly good category). After the post-test, the average target knowledge score increased 10.5% to 81.0. Skill in preparing a balanced menu increased from 78.5 to 89.2. BMI 23.8.5 kg/m2, LP 81.1. Statistical results show significant differences in the level of knowledge and skills in preparing menus before and after the program, but nutritional status is not significant. This shows that PKK cadres can be empowered to implement the IDEA model to prevent obesity in society. Conclusion: there has been an increase in the knowledge and skills of PKK cadres in implementing the IDEAL program.Keywords: obesity, empowerment, cadres, IDEAL program